Bombardment facilities for radioisotope production at the NAC and the production of iron-52, iron-55 and rubidium-81 - Steyn, G. F.(Gideon Francois) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1990.